Interaction Between Different Extracts of Hypericum perforatum L. from Serbia and Pentobarbital, Diazepam and Paracetamol - Aleksandar Rašković; Jelena Cvejić; Nebojša Stilinović; Svetlana Goločorbin-Kon; Saša Vukmirović; Neda Mimica-Dukić; Momir Mikov (Molecules, 2014)
Herb-drug interactions are an important safety concern and this study was conducted regarding the interaction between the natural top-selling antidepressant remedy Hypericum perforatum (Hypericaceae) and conventional drugs. This study examined the influence of acute pretreatment with different extracts of Hypericum perforatum from Serbia on pentobarbital-induced sleeping time, impairment of motor coordination caused by diazepam and paracetamol pharmacokinetics in mice. Ethanolic extract, aqueous extract, infusion, tablet and capsule of Hypericum perforatum were used in this experiment. The profile of Hypericum perforatum extracts as well as paracetamol plasma concentration was determined using RP-HPLC analysis. By quantitative HPLC analysis of active principles, it has been proven that Hypericum perforatum ethanolic extract has the largest content of naphtodianthrones: hypericin (57.77 µg/mL) and pseudohypericin (155.38 µg/mL). Pretreatment with ethanolic extract of Hypericum perforatum potentiated the hypnotic effect of pentobarbital and impairment of motor coordination caused by diazepam to the greatest extent and also increased paracetamol plasma concentration in comparison to the control group. These results were in correlation with naphtodianthrone concentrations. The obtained results have shown a considerable influence of Hypericum perforatum on pentobarbital and diazepam pharmacodynamics and paracetamol pharmacokinetics.